Remediation of petroleum-contaminated soils by fluidized thermal desorption - Lee, JK; Park, D; Kim, BU; Dong, JI; Lee, S (PERGAMON-ELSEVIER SCIENCE LTD, 1998)
A novel type of fluidized bed desorber was developed for the remediation of petroleum-contaminated soils at low temperature with high efficiency. Cahn balance(R) was utilized to investigate the thermal desorption behavior of soils contaminated by various hydrocarbons. The performance of the fluidized-bed desorber was investigated at different operating modes. Batch operation of the fluidized-bed desorber exhibited 99.9% desorption efficiency at temperatures of ca. 300 degrees C within a half hour. Continuous operation of the fluidized-bed indicated that Q/f (the ratio of the mass flow rate of fluidizing gas to feeding rate of contaminated soils) is less important at higher temperature (>300 degrees C), if proper fluidization is ensured. The periodic operation of the fluidized bed desorber shows the possibility to reduce off-gas volume significantly. (C) 1999 Elsevier Science Ltd. All rights reserved.